Mining routinely collected acute data to reveal non-linear relationships between nurse staffing levels and outcomes. Issue 12 (16th December 2016) - Leary, Alison; Cook, Rob; Jones, Sarahjane; Smith, Judith; Gough, Malcolm; Maxwell, Elaine; Punshon, Geoffrey; Radford, Mark
Abstract : Objectives: Nursing is a safety critical activity but not easily quantified. This makes the building of predictive staffing models a challenge. The aim of this study was to determine if relationships between registered and non-registered nurse staffing levels and clinical outcomes could be discovered through the mining of routinely collected clinical data. The secondary aim was to examine the feasibility and develop the use of 'big data' techniques commonly used in industry for this area of healthcare and examine future uses. Setting: The data were obtained from 1 large acute National Health Service hospital trust in England. Routinely collected physiological, signs and symptom data from a clinical database were extracted, imported and mined alongside a bespoke staffing and outcomes database using Mathmatica V.10. The physiological data consisted of 120 million patient entries over 6 years, the bespoke database consisted of 9 years of daily data on staffing levels and safety factors such as falls. Primary and secondary outcomes: To discover patterns in these data or non-linear relationships that would contribute to modelling. To examine feasibility of this technique in this field. Results: After mining, 40 correlations (p<0.00005) emerged between safety factors, physiological data (such as the presence or absence of nausea) and staffing factors. Several inter-related factors demonstrated step changes where registered nurse availability appeared to relate to physiological parameters or outcomes such as falls and the management of symptoms. Data extraction proved challenging as some commercial databases were not built for extraction of the massive data sets they contain. Conclusions: The relationship between staffing and outcomes appears to exist. It appears to be non-linear but calculable and a data-driven model appears possible. These findings could be used to build an initial mathematical model for acute staffing which could be further tested.